2021
DOI: 10.25078/ijhsrs.v5i2.3036
|View full text |Cite
|
Sign up to set email alerts
|

The Community-Based Ecotourism Development on “Taman Beji Griya” in Punggul Village, Abian Semal, Badung

Abstract: <p><br />The community-based ecotourism (CBET) is a new paradigm of tourism to encourage<br />the preservation of nature and culture, as well as improve the economy of local people. The development of CBET “Taman Beji Griya” in Punggul Village which is managed by the extended family community, “Griya Gede Manuaba Punggul”, is the main focus of this study. This CBET combines natural attractions such as waterfalls and caves with malukat and tirtayatra rituals, without changing its socio-religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Efforts to overcome this problem have so far been inadequate because they have not received sufficient attention. Based on his research, (Inten Mayuni et al, 2021)he found that community involvement in line with village functions is very important to provide support for the development of Cemagi Village as a natural tourism area, as explained in the article entitled "Empowerment of the Pakraman Village Community in Efforts to Develop Cemagi Village as a Natural Tourism Area." (Arka et al, 2018)However, the potential of the Pakraman Village community has not been fully realized.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to overcome this problem have so far been inadequate because they have not received sufficient attention. Based on his research, (Inten Mayuni et al, 2021)he found that community involvement in line with village functions is very important to provide support for the development of Cemagi Village as a natural tourism area, as explained in the article entitled "Empowerment of the Pakraman Village Community in Efforts to Develop Cemagi Village as a Natural Tourism Area." (Arka et al, 2018)However, the potential of the Pakraman Village community has not been fully realized.…”
Section: Resultsmentioning
confidence: 99%
“…The stages of the Melukat ceremony include chanting, which has been transcribed and checked by Ida Pandita Agni Bang, who also provided the Mantras used in the ceremony. Some translations were provided by his assistant, Ni Ketut Sunaradi (Mekarini, 2020;Tanu, 2020;Mayuni, 2021).…”
Section: Melukat Ritual Stepsmentioning
confidence: 99%